Effectiveness of Acceptance and Commitment Therapy Management on Self- Differentiation and Mental health among Veterans' Children - Zahra Fakouri Joybari; Ramezan Hasanzadeh; Ghodatollah Abbasi (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Veterans, their spouses and their children suffer from persistent pain and suffering. Many of them face many problems, including mental, physical, and economic, and therefore their general health is likely to be in danger. The purpose of this study was to evaluate the effectiveness of acceptance and commitment therapy on self-differentiation and mental health among veterans' children. Materials and Methods: This research was of semi-experimental design with pre-test, post-test, control group and follow-up. The statistical population of this study included all daughters of veterans who were high schoolstudents. Among the statistical population, 80 students were selected and after the implementation of the GQH-28 questionnaire, and 60 students who with middle and low scores were selected and randomly assigned to two groups, 30 students in the experimental group and 30 in the control group. The experimental group underwent eight sessions of acceptance and commitment therapy. Before and after intervention and the follow-up, tests were performed on groups. Data were analyzed by SPSS software version 22 using covariance analysis. Results: The mean (SD) age of the experimental group was 16.31 (0.7) and the control group was 16.22 (0.6). The mean (SD) self-differentiation score in the pre-test of the experimental group increased from 1332 (18.1) to 177.1 (17.1) in the post-test and 179.5 (15.6) in the follow up (P<0.001), but the mean (SD) self-differentiation scores of the control group was not significantly different in pre-test, post-test and follow-up. The score for the lack of mental health in the experimental group varied from 58.8 (7.1) in the pre-test to 33.2 (6.4) in the post-test and 35.1 (6.6) in follow-up, but the mean (SD) of the mental health scores of the control group did not differ in the pre-test, post-test and follow-up. Conclusion: The study showed that acceptance and commitment therapy leads to increased self-isolation and reduced mental health of veterans'children. DOI: http://doi.org/10.22037/ch.v6i3.24470